PD‐1 is not required for natural or peripherally induced regulatory T cells: Severe autoimmunity despite normal production of regulatory T cells. Issue 12 (27th October 2014) - Ellestad, Kristofor K.; Thangavelu, Govindarajan; Ewen, Catherine L.; Boon, Louis; Anderson, Colin C.
Abstract : The expression of the coinhibitor PD‐1 on T cells is important for the establishment of immune homeostasis. We previously found that PD‐1 is particularly critical for the control of self‐tolerance during lymphopenia‐induced proliferation of recent thymic emigrants (RTEs). Previous studies suggested that PD‐1 modulates the generation of Treg cells, particularly peripherally induced Treg (pTreg) cells, and controls Th17 cells. However, these conclusions were derived indirectly from studies on the ligand PD‐L1, and not PD‐1 itself. Herein we directly tested whether T‐cell PD‐1 expression was needed for Treg cell generation and examined if a paucity of Treg cells or enhanced Th17 cells could explain the severe lymphopenia‐potentiated autoimmunity caused by PD‐1 KO RTEs. Employing the murine FoxP3 EGFP reporter system to simultaneously monitor conversion of WT and PD‐1 KO T cells to pTreg cells in the same animal, we found that PD‐1 deficiency did not inhibit pTreg cell generation or lead to Th17‐cell‐mediated autoimmunity. Surprisingly, pTreg cell numbers were increased in PD‐1 KO versus WT cell populations. Furthermore, we noted an increased conversion to pTreg cells by RTEs. Our data suggest that the primary role for PD‐1 is to restrain T‐cell activation/proliferation to self‐Ags rather than promote generation of Treg cells.